The glitch : a novel - Cohen, Elisabeth (New York : Doubleday, 2018)
"A fast, funny, deeply hilarious debut--The Glitch is the story of a high-profile, TED-talking, power-posing Silicon Valley CEO and mother of two who has it all under control, until a woman claiming to be a younger version of herself appears, causing a major glitch in her over-scheduled, over-staffed, over-worked life. Shelley Stone might be a little overwhelmed. She runs the company Conch, the manufacturer of a small wearable device that attaches to the user's ear and whispers helpful advice and prompts. She's married with two small children, Nova and Blazer, both of whom are learning Mandarin. She employs a cook, a nanny, a driver, and an assistant, she sets an alarm for 2AM conference calls, and occasionally takes a standing nap while waiting in line when she's really exhausted. Shelley takes Dramamine so she can work in the car; allows herself ten almonds when hungry; swallows Ativan to stave off the panic attacks; and makes notes in her day planner to "practice being happy and relatable." But when Shelley meets a young woman named Shelley Stone who has the exact same scar on her shoulder, Shelley has to wonder: Is some sort of corporate espionage afoot? Has she discovered a hole in the space-time continuum? Or is she finally buckling under all the pressure? Introducing one of the most memorable and singular characters in recent fiction, The Glitch is a completely original, brainy, laugh-out-loud story of work, marriage, and motherhood for our times"--
Keywords: Women chief executive officers -- Fiction; Working mothers -- Fiction; FICTION / Humorous; FICTION / Contemporary Women; FICTION / Satire; Humorous fiction